Leadership from the inside out : becoming a leader for life - Cashman, Kevin (Berrett-Koehler Publishers, 2017)
This book serves as an integrated coaching experience that helps leaders understand how to harness their authentic, value-creating influence and elevate their impact as individuals, in teams, and in organizations. Case studies, stories, and exercises are also included.